2012
DOI: 10.1088/0960-1317/22/9/094009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostrictive–piezoelectric composite structures for energy harvesting

Abstract: In this paper, harvesters coupling magnetostrictive and piezoelectric materials are investigated. The energy conversion of quasi-static magnetic field variations into electricity is detailed. Experimental results are exposed for two macroscopic demonstrators based on the rotation of a permanent magnet. These composite/hybrid devices use both piezoelectric and magnetostrictive (amorphous FeSiB ribbon or bulk Terfenol-D) materials. A quasi-static (or ultra-low frequency) harvester is constructed with exploitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…One can also notice the very linear aspect of the curve between 0 and 75 kA=m, which is a predominant parameter to produce a precise dc current sensor using the ME effect [85,88]. This linearity could also be exploited for energy-harvesting purpose with an extremely low-frequency and high-ac field [89].…”
Section: Magnetoelectric Effectmentioning
confidence: 93%
“…One can also notice the very linear aspect of the curve between 0 and 75 kA=m, which is a predominant parameter to produce a precise dc current sensor using the ME effect [85,88]. This linearity could also be exploited for energy-harvesting purpose with an extremely low-frequency and high-ac field [89].…”
Section: Magnetoelectric Effectmentioning
confidence: 93%
“…Lafont et al [6] show how magnetostriction and piezoelectricity can be combined to harvest energy from slow continuous motion. Others are focusing on higher rotation frequencies, e.g.…”
Section: B Related Workmentioning
confidence: 99%
“…Piezoelectric-and magnetostriction harvesters rely on induced strain that can generate electrical charges or change a in permeability respectively. The strain in the material can be induced by mechanically stress the material or as Lafont et al [6] showed by laminating magnetostrictive and piezoelectric materials, which can induce strain by introducing a varying magnetic field.…”
Section: Description Of Energy Harvesting Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Today Terfenol-D is experiencing a renewal with high performance multiferroïc composite materials combining high magnetostriction and piezoelectric constants. Composites of Terfenol-D and PZT can produce exploitable amounts of electrical energy to supply low-power electronics [1,2]. Terfenol-D manufacturing techniques must meet new criteria, i.e., miniaturization and low cost, while maintaining high strain performance.…”
Section: Introductionmentioning
confidence: 99%